Properties of hydroxypropylated normal wheat, waxy wheat, and waxy maize starches and an improved 1H NMR method to determine level of hydroxypropyl groups - Wang, Weiwei (Kansas State University, 2019)
Waxy wheat starch (WWS) containing little or no amylose has unique properties for food and industrial uses. Hydroxypropylation, a widely used means for modifying starches, could enhance functionalities of starch by substituting hydroxyl groups in starch. There are limited numbers of literatures regarding hydroxypropylation of WWS. WWS hydroxypropylated with 3.0-9.0% propylene oxide (PO) were prepared and compared to hydroxypropylated normal wheat starch (NWS) and hydroxypropylated waxy maize starch (WMS). The molar substitution (MS) of the resulting hydroxypropylated NWS, WWS and WMS was 0.055-0.151, 0.048-0.133, and 0.049-0.139, respectively. Gelatinization temperatures and enthalpy of hydroxypropylated starches were significantly lower than those of their unmodified counterparts and the extent of decrease was positively correlated to the MS. Differential scanning colorimetry (DSC) results showed that hydroxypropylation reduced the retrogradation of the starches during the storage after gelatinization but there were differences between the starches. For the same level of PO reaction (3 and 5% PO), hydroxypropylated WWS retrogradated less than hydroxypropylated WMS, suggesting that for the same level of cold storage stability, less PO is needed for WWS. After reacted with 6% PO, MS was 0.092 and 0.094, respectively, for WWS and WMS, and no retrogradation was observed for those hydroxypropylated starches, indicating that at MS ~0.094, hydroxypropyl groups prevents amylopectin chains from re-associating and forming crystalline structures. In contrast, a higher level of PO (9%) was needed to react with NWS to achieve the hydroxypropylated starch with an MS of 0.151 that gave no retrogradation. Consistent with microscopic observation results, Micro-Visco-Amylograph (MVA) analysis showed hydroxypropylated starches developed viscosity at lower temperatures and had improved hot and cold viscosities. The specific characteristics of hydroxypropylated starches are related to the degree of hydroxypropylation. Therefore, it is critical to determine the level of hydroxypropylation in modified starches. ¹H NMR is a simple and rapid means of determining hydroxypropyl (HP) group in modified starches. In this study, a method to prepare a HP starch for NMR analysis was improved. The optimum parameters proposed to hydrolyze HP starches were 10% starch solid content, 3.5% (wt.%) DCl in D₂O as the solvent, sodium acetate as an internal standard, heating at 90oC for 1 h. Optionally, 6% (v/v) trifluoroacetic acid-d as the water-peak shifting reagent. Six hydroxypropylated starch samples and two commercial cross-linked and hydroxypropylated starch samples were hydrolyzed with this modified method before ¹H NMR analysis, and the results of HP group content in the samples were in agreement with the results from an enzyme-catalyzed method, which indicate that the improved acid hydrolysis method is applicable for both hydroxypropylated starch and cross-linked and hydroxypropylated starch.
Keywords: Hydroxypropylated starch; Acid hydrolysis; Waxy wheat starch; Molar substitution; 1H NMR; Retrogradation